Increasing Programming Self-Efficacy (PSE) Through a Problem-Based Gamification Digital Learning Ecosystem (DLE) Model - Siwalai Chinchua; Thiyaporn Kantathanawat; Somkiat Tuntiwongwanich (My University, 2022)
The researchers initially undertook a systematic literature review concerning problem-based learning (PBL), gamification, digital learning ecosystems (DLE), and programming self-efficacy (PSE). Using recent studies and papers from Google Scholar, a preliminary gamified and DLE model was proposed to help Thai students PSE. Further analysis was conducted on gamification mechanics, dynamics, and aesthetics (MDA). After an assessment by nine educational experts using four educational assessment tools from the Joint Committee on Standards for Educational Evaluation (JCSEE) of the proposed seven-step A3S3R (advise, assign, analyze, search, synthesize, summarize, and report) DLE Management Model, the model's suitability was judged to be 'very high' (mean = 4.40, SD = 0.59). Consequently, the development of this learning management model will result in learners recognizing their abilities better in programming and having better programming skills. It can also potentially increase students' critical and analytical thinking skills and computational thinking and allow them to apply new knowledge or skills to new situations. Finally, researchers can develop new practical learning styles for use in teaching and learning.
Keywords: Computational Thinking; Educational Games and Gamification